2021
DOI: 10.3352/jeehp.2021.18.8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the use of manikins and simulated patients in a multidisciplinary in situ medical simulation program for healthcare professionals in the United Kingdom

Abstract: Purpose: Simulation training is increasingly popular in healthcare education, and often relies on specially designed manikins. However, it is also possible to work with actors, or simulated patients (SPs), which may provide a greater sense of realism. This study aimed to compare these 2 approaches, to ascertain which makes healthcare professionals feel most comfortable, which leads to the greatest improvement in confidence, and which is most beneficial to learning.Methods: This study was embedded in a pre-exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…In the present study, we found that the greatest realism perceived by both students and teachers was for the simulated participant (actress), although this result was not statistically significant in the sample of students and strongly significant in the sample of teachers. Similar results were reported by Meerdink and Khan, who carried out a study comparing scenarios performed with actors or with manikins and found that the use of actors was much more realistic, favoring learning results, especially in the aspect of communication [ 14 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, we found that the greatest realism perceived by both students and teachers was for the simulated participant (actress), although this result was not statistically significant in the sample of students and strongly significant in the sample of teachers. Similar results were reported by Meerdink and Khan, who carried out a study comparing scenarios performed with actors or with manikins and found that the use of actors was much more realistic, favoring learning results, especially in the aspect of communication [ 14 ].…”
Section: Discussionsupporting
confidence: 83%
“…This also generates a decrease in stress among students and increases excitement and enthusiasm by making them direct participants in the learning process [ 13 ]. On the other hand, there are studies that prefer the use of standardized patients versus mannequins because they confer greater realism [ 14 ] and lead to significant differences in performance and in the acquisition of most skills [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…These strategies include the use of standardized patients, exposure to patient care through observation, and increasingly manikin-based SPEs. [11][12][13] These strategies are typically used in combination, such that knowledge acquisition occurs with concepts presented over time and occur in different learning environments. 8,10 Although the use of manikin-based SPEs have been adopted by most medical schools in the United States, there is significant heterogeneity by which such exercises are conducted and evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…An SP refers to a person trained to portray a patient or another person (such as a relative, member of the public or allied healthcare professional) in a simulation environment. The term "actor" is often used to describe an SP involved in a simulation, but the role of an SP differs from traditional acting roles in that they are part of the educational team and have a role in achieving the learning outcomes of each specific simulation (Table 1) [3][4][5].…”
Section: Introduction Background/rationalementioning
confidence: 99%
“…The use of an SP creates a more realistic interaction between the patient and learner and enhances the training experience when compared to using manikins [4]. Furthermore, an SP provides feedback when debriefing a simulation, including how it felt to interact with the learners as a patient.…”
Section: Introduction Background/rationalementioning
confidence: 99%